ANALYSIS OF TEACHER DISCRIMINATION AGAINST STUDENTS OF SOCIAL STUDIES DEPARTMENT IN CENTRAL KALIMANTAN - Rebekah Anggreni (STKIP PGRI Situbondo, 2023)
The program carried out in SMA (Junior High School) is an effort to develop students' abilities. However, in its implementation, majors in Junior High School actually cause discriminatory actions against students majoring in social studies (Social Sciences) so that negative labels or stamps appear on students who take the major, both in the school environment and in the community. This study was conducted to find out :1). Causes of discriminatory occurrence in the school environment, 2). Impact on negative stamps/labels of the school environment. The method used is a qualitative method with a direct interview study type in the field. By seeking information from three (3) subjects/speakers, including two students and a permanent teaching teacher there at the high school. The negative label given to students majoring in social studies does not just happen, but there is a cause. The social sanctions given by the school environment stem from the attitudes and behaviors of children majoring in social studies that are not good, and tend to deviate from school rules or regulations.